STRATEGI PEMASARAN UNTUK MENINGKATKAN PENJUALAN PRODUK KERIPIK PISANG 'MERASA' DI KABUPATEN TANJUNG JABUNG TIMUR - Marsya, Andi; Arif Musthofa, M.; Nurjali, Nurjali; Wandi (Jurnal Dinamika Ekonomi Syariah, 2025)
This research is motivated by the high level of competition among entrepreneurs, especially traders, in attracting consumer attention in order to increase sales. One solution that can be applied is an effective and efficient marketing strategy. This marketing strategy focuses on four main elements known as the marketing mix, namely product, pricing, distribution policy, and promotion. The marketing mix has an important role in ensuring the survival of a business. However, in practice, marketing strategies are often still based on conventional economic principles. Therefore, this study aims to analyze the application of marketing strategies in increasing sales. This study uses a qualitative method with a type of field research. Primary data were obtained through interviews with business owners, employees, and prospective business successors, namely the children of the owner of the banana chips business "Merasa." Meanwhile, secondary data were obtained from various relevant written reference sources. Data collection methods used in this study include interviews, observations, and documentation. The results of data analysis show that marketing strategies in increasing sales can be seen from three main aspects, namely: product strategies that focus on quality and innovation, pricing strategies that set competitive prices, and promotional strategies carried out to expand market reach. Thus, the right and targeted marketing strategy can be the main key in increasing sales and supporting the sustainability of the "Merasa" banana chips business.